2015
DOI: 10.3390/w7073515
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Corrosive Action of Mineral Waters from Thermal Sources: A Case Study at Azores Archipelago, Portugal

Abstract: Abstract:Waters from natural sources of the São Miguel Island in the Azores archipelago have been investigated regarding their corrosive action on metallic materials. The corrosive and encrusting characteristics of the waters have been established in terms of relevant chemical parameters (namely pH, conductivity, total dissolved solids (TDS), and concentrations of bicarbonate, calcium, magnesium, chloride, and sulfate ions) and their temperature by using Langelier, Ryznar, Puckorius and Larson-Skold indexes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Previous studies [15,39] have indicated the importance of the selection of pipe material in water systems with high corrosiveness, among others, on the basis of water quality parameters, such as pH, alkalinity, and calcium hardness. The presented approach has been proven to be suitable for assessing the corrosive properties of mineral waters, as confirmed by analysis shown in [40,41]. The mentioned research shows the need for the broad characterization of mineral water compositions, including their aggressiveness concerning different materials, using the analyzed indices, which in turn will help to establish criteria for categorizing stability of the water [42,43].…”
Section: Results For Assessment Of the Resistance Of Installation Materials To The Corrosive Effects Of Mineral Watersmentioning
confidence: 59%
“…Previous studies [15,39] have indicated the importance of the selection of pipe material in water systems with high corrosiveness, among others, on the basis of water quality parameters, such as pH, alkalinity, and calcium hardness. The presented approach has been proven to be suitable for assessing the corrosive properties of mineral waters, as confirmed by analysis shown in [40,41]. The mentioned research shows the need for the broad characterization of mineral water compositions, including their aggressiveness concerning different materials, using the analyzed indices, which in turn will help to establish criteria for categorizing stability of the water [42,43].…”
Section: Results For Assessment Of the Resistance Of Installation Materials To The Corrosive Effects Of Mineral Watersmentioning
confidence: 59%
“…In relation to the LSI, the Ryznar stability index broadens the range of parameters liable to affect corrosion and water hardness because it considers magnesium content, temperature and dry residue, which indirectly considers typical components of dissolved substances, i.e., chlorides and sulfides. The RSI has a more extended corrosivity range than the LSI: 4 < RSI < 5-strong precipitation of sediment, 5 < RSI < 6-medium precipitation of sediment, 6 < RSI < 7-weak precipitation of sediment or initial corrosion, 7 < RSI < 7.5corrosion, 7.5 < RSI < 9-strong corrosion, RSI > 9-very strong corrosion [56,57,[68][69][70][71]. Basing on the performed determinations of quality parameters of the water transported by the investigated cast-iron pipelines (Table 1), the Langelier saturation index was calculated, which amounted to 0.07, which indicates very low precipitatibility, whereas the Ryznar index amounted to 7.17, which indicates very low corrosive features of the water flowing through the investigated pipelines.…”
Section: Discussionmentioning
confidence: 99%
“…Water is aggressive when the I value is greater than 1.0. Another indicator that describes the corrosivity of water is the Langelier Saturation Index (LSI) [16]. It is an indicator of the possibility of scale formation in the water.…”
Section: One Of the Basic Indicators Of Water Corrosivity Is The Acid...mentioning
confidence: 99%
“…The measure of the influence of the actual pH, the concentration of calcium, bicarbonate, TDS, and temperature forms another index called the Ryznar Stability Index (RSI) [16], expressed as: RSI = 2(pH s ) − pH In this equation, a value below 5 indicates water instability, and a CaCO 3 sediment forming capacity, and thus the corrosivity of the water, is lowered. Within 5-7, the depleting CaCO 3 does not form a sediment, the water is corrosive, and sub-sediment corrosion may occur.…”
Section: One Of the Basic Indicators Of Water Corrosivity Is The Acid...mentioning
confidence: 99%